Classic tailoring techniques for menswear : a construction guide - Antoine, Denis; Cabrera, Roberto (Fairchild Books, 2022)
"Since its first publication, Classic Tailoring Techniques for Menswear has been the authoritative resource for custom hand tailoring production. Providing in-depth, step-by-step instructions for the processes required by bespoke and couture-level manufacturing, this book retains its value and relevance for young and established tailors alike. Continuing this great tradition, the third edition introduces new discussions of traditional tailoring processes in the industry and highlights the value of hand-crafted construction in the context of environmentally-sustainable design. New features include Learning Objectives in each chapter, boxes highlighting Tricks of the Trade, end of chapter discussion questions, as well as a renewed focus on essential vocabulary, including an extended glossary"- Resumé vydavatel
Obsahuje online acces code
Terminologický slovník
Keywords: krejčovství; pánské oděvy; tailors trade; men’s clothing; příručky; handbooks and manuals